Increasing the Rate of Magnesium Intercalation Underneath Epitaxial Graphene on 6H‐SiC(0001). Issue 23 (10th November 2021) - Kotsakidis, Jimmy C.; Currie, Marc; Grubišić‐Čabo, Antonija; Tadich, Anton; Myers‐Ward, Rachael L.; DeJarld, Matthew; Daniels, Kevin M.; Liu, Chang; Edmonds, Mark T.; Vázquez de Parga, Amadeo L.; Fuhrer, Michael S.; Gaskill, D. Kurt
Abstract: Magnesium intercalated "quasi‐freestanding" bilayer graphene on 6H‐SiC(0001) (Mg‐QFSBLG) has many favorable properties (e.g., highly n‐type doped, relatively stable in ambient conditions). However, intercalation of Mg underneath monolayer graphene is challenging, requiring multiple intercalation steps. Here, these challenges are overcome and the rate of Mg intercalation is significantly increased by laser patterning (ablating) the graphene to form micron‐sized discontinuities. Low energy electron diffraction is then used to verify Mg‐intercalation and conversion to Mg‐QFSBLG, and X‐ray photoelectron spectroscopy to determine the Mg intercalation rate for patterned and non‐patterned samples. By modeling Mg intercalation with the Verhulst equation, it is found that the intercalation rate increase for the patterned sample is 4.5 ± 1.7. Since the edge length of the patterned sample is ≈5.2 times that of the non‐patterned sample, the model implies that the increased intercalation rate is proportional to the increase in edge length. Moreover, Mg intercalation likely begins at graphene discontinuities in pristine samples (not step edges or flat terraces), where the 2D‐like crystal growth of Mg‐silicide proceeds. The laser patterning technique may enable the rapid intercalation of other atomic or molecular species, thereby expanding upon the library of intercalants used to modify the characteristics of graphene, or other 2D materials and heterostructures. Abstract : Patterning epitaxial monolayer graphene using a femtosecond pulsed laser to remove micrometer sized areas of graphene results in a significant increase in the rate of magnesium intercalation. Using X‐ray photoelectron spectroscopy, a model based on the Verhulst equation shows that the increased intercalation rate of Mg is proportional to the increased edge length of the patterned graphene sample.